Strength and performance perception differences between four phases of the menstrual cycle - Jacobson, B. H.; Lentz, W.; Kulling, F. A. (Medicine & Science in Sports & Exercise, 1998)
Female varsity athletes (N = 6) not using oral contraceptives were measured for strength and selected performances during four phases of the menstrual cycle. Strength was measured by repetitions of quadriceps knee extensions of the dominant leg. A five-point semantic differentiation scale comprising 10 sets of descriptive polar terms was used to analyze perceived physical variances. Average strength was significantly lower in the premenstrual phase. During this phase perceptions of strength, power, and speed were also lower. Implication. In the premenstrual phase females perceive lower performance capabilities that are matched by reductions in their actual performances.